Hubungan Pengetahuan dengan Keaktifan Kader dalam Kegiatan Posyandu di Wilayah Kerja UPT Puskesmas Kereng Bangkirai Kota Palangka Raya: The Correlation of Knowledge with Cadre’s Activeness in Integrated Healthcare Center (Posyandu) Activities in The Working Area of Public Health Center (Puskesmas) of Kereng Bangkirai, Palangka Raya - Iitdrie Iitdrie; Lensi Natalia Tambunan; Eva Prilelli Baringbing (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The Integrated Healthcare Center (Posyandu) is a form of community-based health effort managed and organized from, by, for, and with the community in the implementation of health, development to empower the community and provide convenience to the community in obtaining basic health services. The continuity of Posyandu cannot be separated from the role of cadres, who are the spearhead of all activities at Posyandu. However, not all cadres are active in carrying out their duties. The study aimed to determine the correlation between knowledge and the activeness of cadres in Posyandu activities. The survey used in this study is an analytical survey with a cross-sectional approach. In addition, the sampling technique used is total sampling, which is all Posyandu’s cadres in the research location with a total of 51 people. Furthermore, the analysis is univariate and bivariate with a chi-square test. The chi-square test result shows a p-value of 0.008 <0.05, which means there is a correlation between knowledge and the activeness of cadres in Posyandu activities in the working area of the Public Health Center (Puskesmas) of Kereng Bangkirai. As there is a correlation between knowledge and the activeness of cadres in Posyandu activities, the suggestions that can be given by the author are: giving training by the health workers in the working area of the local Puskesmas, giving refreshing for the cadres periodically with topics related to Posyandu, and giving attention from the local government regarding the welfare of cadres as an effort to motivate cadres.